THE EFFECT OF FISHBONE STRATEGY ON STUDENTS’ ACHIEVEMENT IN WRITING ANALITYCAL EXPOSITION TEXT - Lewi Sidabutar; Siti Aisah Ginting (Universitas Negeri Medan, 2016)
The objective of this study was to find out whether there was a significant effectof Fishbone Strategy on students’analytical exposition writing ability. It wascunducted by using experimental research. The population of this study waseleventh grade of SMA N 1 Girsang Sipangan Bolon, which is consisted of 4parallel classes. Two classes were taken as a sample of the research. The class XIIPA 1 was an experimantal group and class XI IPA 3 as a control group. Theexperimental group was taught by using Fishbone Strategy, otherwise controlgroup was taught by using Discussion Method. The instrument for collecting datawas writing test. The data was analyzed by using t-test formula. The result showsthat the value of t-obseved is higher than the value of t-table. (3,69>1,701(α =0,05)) with the degree of freedom (df) = 54. Based on the data analysis of thestudy, the result indicates that Fishbone Strategy affects on students’ analyticalexposition writing ability.